2021
DOI: 10.46234/ccdcw2021.242
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insight into the Antimicrobial Resistance of <i>Streptococcus Suis</i> — Six Countries, 2011–2019

Abstract: What is already known on this topic? Streptococcus suis ( S. suis ) is a zoonotic pathogen causing disease in humans and animals, and the emergence of its increased resistance to antimicrobial agents has become a significant challenge in many countries. What is added by this report? Using whole genome sequencing data to accurately predict antimicrobial resistance determinants, it was found that the prevalence of antimicrobial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The most prevalent AMR element found among the isolates was tetO, followed by ermB, lsaE, lnuB, ant(9)-Ia, and ant(6)-Ia. While differences in MICs between countries have been described, high prevalence rates for macrolide and tetracycline resistance, along with low prevalence rates for β-lactam resistance have been previously reported (Gurung et al, 2015;Aradanas et al, 2021;Dechene-Tempier et al, 2021;Hadjirin et al, 2021;Ma et al, 2021;Matiasovic et al, 2021;Cucco et al, 2022). This has been a global trend for several decades now, and the genetic basis for these resistances has been extensively studied (Varela et al, 2013;Gurung et al, 2015;Seitz et al, 2016;Dechene-Tempier et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The most prevalent AMR element found among the isolates was tetO, followed by ermB, lsaE, lnuB, ant(9)-Ia, and ant(6)-Ia. While differences in MICs between countries have been described, high prevalence rates for macrolide and tetracycline resistance, along with low prevalence rates for β-lactam resistance have been previously reported (Gurung et al, 2015;Aradanas et al, 2021;Dechene-Tempier et al, 2021;Hadjirin et al, 2021;Ma et al, 2021;Matiasovic et al, 2021;Cucco et al, 2022). This has been a global trend for several decades now, and the genetic basis for these resistances has been extensively studied (Varela et al, 2013;Gurung et al, 2015;Seitz et al, 2016;Dechene-Tempier et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The 89 K pathogenicity island (89 K PAI) carried by Chinese epidemic strains is an example of a S. suis MGE harboring factors contributing to a highly invasive phenotype ( Chen et al, 2007 ; Schmid et al, 2011 ). AMR has been extensively reported for S. suis isolates worldwide and many of the genes conferring AMR are passenger genes carried on MGEs ( Palmieri et al, 2011a ; Gurung et al, 2015 ; Huang et al, 2016b , 2018 ; Pan et al, 2019 ; Aradanas et al, 2021 ; Dechene-Tempier et al, 2021 ; Hadjirin et al, 2021 ; Ma et al, 2021 ). For this reason, S. suis is regarded a reservoir for AMR that can be easily transferred to other bacterial commensals and pathogens ( Palmieri et al, 2011b ; Varela et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two aminoglycoside-resistance genes ( ant(6)-Ia and aph(3')-III ) were additionally detected in the porcine strain ID35541. The prevalence and number of antimicrobial resistance genes have been shown to be variable among the different serotypes 25 . In addition, several studies have shown that the genes tet(O) and erm(B) are widely observed among pig and human S. suis isolates of various serotypes worldwide 18 , 25 29 .…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence and number of antimicrobial resistance genes have been shown to be variable among the different serotypes 25 . In addition, several studies have shown that the genes tet(O) and erm(B) are widely observed among pig and human S. suis isolates of various serotypes worldwide 18 , 25 29 . The genes ant(6)-Ia and aph(3')-III have been reported in several S. suis strains isolated from pigs in Canada, China, Korea, and Thailand 17 , 25 , 28 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, antimicrobial resistance (AMR) is an important public health concern. Resistance to tetracyclines, macrolides, and aminoglycosides was isolated at high rates in S. suis , particularly tetracycline and erythromycin, which are encoded by the resistance genes erm(B) and tet(O) [ 41 , 42 ]. One of the crucial problems of antimicrobial resistance is the horizontal transfer of AMRGs.…”
Section: Discussionmentioning
confidence: 99%